A functional long‐term 2D serum‐free human hepatic in vitro system for drug evaluation. (3rd October 2020) - Oleaga, Carlota; Bridges, L. Richard; Persaud, Keisha; McAleer, Christopher W.; Long, Christopher J.; Hickman, James J.
Abstract: Human in vitro hepatic models generate faster drug toxicity data with higher human predictability compared to animal models. However, for long‐term studies, current models require the use of serum and 3D architecture, limiting their utility. Maintaining a functional long‐term human in vitro hepatic culture that avoids complex structures and serum would improve the value of such systems for preclinical studies. This would also enable a more straightforward integration with current multi‐organ devices to study human systemic toxicity to generate an alternative model to chronic animal evaluations. A human primary hepatocyte culture system was characterized for 28 days in 2D and serum‐free defined conditions. Under the studied conditions, human primary hepatocytes maintained their characteristic morphology, hepatic markers and functions for 28 days. The acute and chronic administration of known drugs validated the sensitivity of the system for drug testing. This human 2D model represents a realistic system to evaluate hepatic function for long‐term drug studies, without the need of animal serum, confounding variable in most models, and with less complexity and resultant cost compared to most 3D models. The defined culture conditions can easily be integrated into complex multi‐organ in vitro models for studying systemic effects driven by the liver function for long‐term evaluations.